(untitled) (Ágora de Heterodoxias, 2016)
Accelerograms data of earthquakes with magnitudes Mw≥7 are not yet registered for the coast of Ecuador. The seismological network in this country, which started its operation in 1988, has only registered a strong earthquake: The Bay of Caráquez of August 4, 1998 (Mw 7.2). Bahia de Caraquez is located in the province of Manabi, and accelerometers available in the region did not track as appropriate this earthquake, it only has a record obtained in Guayaquil, which is approximately 250 km from the epicenter, but no data near-field record are available. Consequently, research whose results are reported in this article has been applied to inter-plate tectonic low angle model type "Thrust", delineating the displacement fault plane, which has led to identified the earthquake response spectrum. In this research also has been used as a reference, earthquakes with tectonic scenario similar to those of the central coast of Ecuador, ranging from short periods, applying the model of weighted averages, which subsequently subduction earthquakes were scaled in the continental Peruvian margin 1966 (Mw 8.1), 1970 (Mw 7.9), 1974 (Mw 8.0) and 2007 (Mw 7.9). In this sense, we want to know the methodology and be able to scale earthquakes of similar magnitudes with an equation of strong motions for “Thrust” type inter-plate sources.